Improved Performance Cooling System with Integrated Condenser and Direct Evaporator Cooling - Arfidian Rachman (Jurnal Teknik Mesin, 2019)
For areas with very hot and humid weather conditions increased latent and sensible loads are a major problem in cooling systems that will increase compressor work so that electricity consumption will also increase. Combined Condenser with direct evaporative cooling will increase the heat removal process by using an evaporative cooler effect that will increase the efficiency of energy use. This paper presents the study of the use of evaporative cooling and condenser. This paper mainly calculated energy consumption in steam compression cooling systems and related problems. From the results of this study, the use of condensers with evaporative cooling, power consumption can be reduced to 46% and performance of coefficient (COP) can be increased by about 12%, with 1,2 kW cooling capacity.